Distinguishing adolescents who think about self-harm from those who engage in self-harm. - O'Connor, R; Rasmussen, S; Hawton, K (2012)
BACKGROUND: Adolescent self-harm is a major public health concern, yet little is known about the factors that distinguish adolescents who think about self-harm but do not act on these thoughts from those who act on such thoughts. AIMS: Within a new theoretical model, the integrated motivational-volitional model, we investigated factors associated with adolescents having thoughts of self-harm (ideators) v. those associated with self-harm enaction (enactors). METHOD: Observational study of school pupils employing an anonymous self-report survey to compare three groups of adolescents: self-harm enactors (n = 628) v. self-harm ideators (n = 675) v. those without any self-harm history (n = 4219). RESULTS: Enactors differed from ideators on all of the volitional factors. Relative to ideators, enactors were more likely to have a family member/close friend who had self-harmed, more likely to think that their peers engaged in self-harm and they were more impulsive than the ideators. Enactors also reported more life stress than ideators. Conversely, the two self-harm groups did not differ on any of the variables associated with the development of self-harm thoughts. CONCLUSIONS: As more adolescents think about self-harm than engage in it, a better understanding of the factors that govern behavioural enaction is crucial in the effective assessment of the risk of self-harm.